Exploitation of magnetic dipole resonances in metal–insulator–metal plasmonic nanostructures to selectively filter visible light - Pinton, N; Grant, J; Collins, S; Cumming, DRS (American Chemical Society, 2018)
Significant improvement in using plasmonic nanostructures for practical color filtering and multispectral imaging applications is achieved by exploiting the coupling of surface plasmons with dielectric optical cavity resonances within a hexagonal array of subwavelength holes in a thin CMOS-compatible metal–insulator–metal stack. This polarization-independent architecture overcomes the limitations of all previously reported plasmonic color filters, namely poor transmission and broad band-pass characteristic, effectively providing a compact approach for high color accuracy multispectral and filtering technologies. Measured transmission efficiencies up to 60% and full-width at half-maximum between 45 and 55 nm along the entire visible spectrum are achieved, an impressive and unique combination of features that has never been reported before. The nanostructure exploits the phenomenon of extraordinary optical transmission and magnetic dipole modes to efficiently filter visible light. The presence of magnetic resonances in the optical regime is an unusual property, previously reported in photonic metamaterials or dielectric nanoparticles. The physical insights established from the electromagnetic near-field patterns are used to accurately tailor the optical properties of the filters. The nonideality of the fabrication at the nanoscale is addressed, the issues encountered highlighted, and alternative solutions proposed and verified, demonstrating that the working principle of the MIM structure can be successfully extended to other materials and structural parameters.